Mapping multidimensional excited state dynamics using pump-impulsive-vibrational-spectroscopy and pump-degenerate-four-wave-mixing - Kraack, Jan Philip; Wand, Amir; Buckup, Tiago; Motzkus, Marcus; Ruhman, Sanford (Physical chemistry, chemical physics, 2013)
Pump-impulsive vibrational spectroscopy (pump-IVS) is used to record excited state vibrational dynamics following photoexcitation of two carotenoids, β-carotene and lycopene, with <30 fs temporal resolution, and covering the full vibrational spectrum of the investigated chromophores. The results record the course of S2-S1 internal conversion, followed by vibrational relaxation and decay to the electronic ground state. This interpretation is corroborated by comparison with pump-degenerate-four-wave-mixing (pump-DFWM) experiments on the same systems. The results demonstrate the potential of both time-domain spectroscopic techniques to resolve photochemical dynamics, including fingerprint frequencies which directly reflect changes in bonding and structure in the nascent sample. The exclusive strengths and limitations of these two methods are compared with those presented by the frequency-domain Femtosecond Stimulated Raman Scattering (FSRS) technique, highlighting the complementary nature of the three, and the benefits of using them in concert to investigate vibrational dynamics in reactive species.
Gesehen am 03.11.2021